Status of Clinical Neuropsychology Training in Finland - Hokkanen, Laura; Jokinen, Hanna; Rantanen, Kati; Nybo, Taina; Poutiainen, Erja (Frontiers in Psychology, 2022)
This paper provides information on different training models within clinical neuropsychology in Finland. Systematic specialization training program began in Finland in 1983. It was first organized mainly by the Finnish Neuropsychological Society and since 1997 by the Finnish universities. At present, close to 400 clinical neuropsychologists have completed the training. The number of professionals still does not cover the needs of the country (population 5.5 million, area 338,440 km²), and geographical disparities are a constant concern. The training models in Finland have changed over the years and will continue to evolve. Specialization training can be organized by national societies or by universities. It can lead to an academic degree or a diploma. It can be linked to doctoral studies or form a parallel track. Financial model can involve student fees or be governed by ministries (such as the Ministry of Education or Ministry of Health). This paper describes and compares different strategies in education that have impact on the output of professionals. One model does not fit all, or even one country at all times. The strategies of the stakeholder ministries can change over time. The experiences from Finland can be useful for other countries that are developing their models. The estimated need of practitioners and the educational resources including the available financial models for training differ between countries. The guiding principles in specialist training should focus on the advanced competencies expected from the neuropsychologist when entering the profession.